Avaliação histopatológica, molecular e bioquímica do fígado, baço e centros melanomacrofágicos do peixe Teleósteo Prochilodus argenteus como biomarcadores de impacto ambiental no rio São Francisco - Heder Jose Ribeiro (2011)
Histolpathological features of the liver, spleen and melanomacrophage centers (MMC) of the teleost fish Prochilodus argenteus and their possible association with biochemical and molecular responses were investigated in animals collected from two different points of the river San Francisco downstream to the Três Marias dam. In each site of the study phisico-chemical analyses from the water and sedment were also performed. In loco liver and splenic fragments were either fixed in Bouin's and Karnovsky liquid for morphological studies, or frozen in dry ice for biochemical and molecular analyses. Morphometric analyses were performed to characterize the structure of the liver and spleen. Our results showed significant differences in the liver cytoarchitecture and in the composition of MMCs between the different studied organs. Pathological events were more frequently seem in the animals from the site immediately downstream of the dam being related with the worst environmental quality associated with the presence of heavy metals in the water and sediment. The size, amount of MMCs and their granule composition were also evaluated. Our results suggest that differences in environmental factors may act adjuvant promoting changes in the hepatic cytoarchitecture of the species P.argenteus. The liver and MMC of this species presents differences among the collection sites, which t can be used as tool in the evaluation of environmental changes.